PTU-109 Development and implementation of the UK national endoscopy database (NED). Issue 2 (June 2019) - Siau, Keith; Lee, Thomas JW; Esmaily, Shiran; Docherty, James; Stebbing, John; Brookes, Matthew J; Broughton, Raphael; Rogers, Peter; Dunckley, Paul; Rutter, Matthew D
Abstract : Introduction: The UK National Endoscopy Database (NED) is a JAG-led informatics project centred on the extraction of data from endoscopy reporting systems (ERS) in participating units to a centralised database. The aim of NED is to facilitate quality assurance, service intelligence, research and training in endoscopy. Herein, we present an overview of the development and implementation of NED from its inception to date, with updates on future directions. Methods: The NED project began in 2013 with the support of UK stakeholder societies. ERS companies were collectively approached to engage in software modification to enable automated uploads of a standardised minimum dataset to NED without patient identifiable data. Since the national roll-out of pilot NED in 2017, endoscopists and organisational leads from services uploading to NED have been able to review key performance indicators on a web-based platform for quality assurance. Results: As of February 2019, 339 out of a total of 529 JAG-registered UK endoscopy units (64%) have actively uploaded to NED. The database comprises over 800, 000 procedures (gastroscopy: 348, 000; sigmoidoscopy: 282, 000; colonoscopy 167, 000; ERCP: 12, 000) and presents procedure-specific KPIs which can be accessed at individual, unit, regional and national levels. Trends in procedural uploads since 2017 are shown in Abstract PTU-109 Figure 1. The functionality of mapping trainee and trainer specific data into the JETS training e-portfolio is undergoing final phase validation, with the objective of providing reliable and unbiased training data to support training and certification. Consultation with multisociety stakeholders and ERS companies on additional data points for NED iteration 2 (NEDi2) is underway. These are intended to expand on existing KPIs, in addition to providing support for polypectomy, ERCP and EUS in line with UK-relevant quality standards. Conclusions: With the engagement of ERS companies, it is possible to implement an automated system to extract data from individual endoscopy units to a centralised database. This has the potential to facilitate endoscopy quality assurance and research at a national level.